Pengaruh Kinerja Keuangan Terhadap Penerimaan Dana Insentif Daerah Pada Pemerintah Provinsi Di Indonesia - Putu Ria Septiani; Rindu Rika Gamayuni (Student Scientific Creativity Journal, 2023)
This study aims to prove empirically the effect of financial performance on the receipt of Regional Incentive Funds in provincial governments in Indonesia. Measurement of financial performance uses the Regional Financial Independence Ratio and the Regional Expenditure Efficiency Ratio. The research method used is quantitative method with sample selection using purposive sampling technique in order to obtain 30 provincial governments as research samples within 3 years. The data analysis method used is multiple linear analysis using IBM SPSS Statistics 26. The results of this panel research are that simultaneously the Independence Ratio and the Efficiency Ratio have a positive effect on Regional Incentive Funds. Partially, the Regional Financial Independence Ratio which compares Regional Original Income to total regional income has a positive and significant effect on Regional Incentive Funds. The Regional Expenditure Effectiveness Ratio which compares the realization of regional expenditures to the regional expenditure budget partially has a positive and significant effect on Regional Incentive Funds.